Assessment of cultural properties in Davao City revisiting tangible and immovable built-heritage for the application of the burra charter process of conservation - Manalang, Aaron Jude M. (2019)
This study was conducted to provide an updated documentation of existing cultural properties and its significance to the community of Davao City. The key objective of this study was to be able to gather data through various methods to formulate and develop specific set of guidelines for conservation of specific cultural properties in Davao city. These specific guidelines follow and utilizes the examples of the Australian Burra Charter process of Conservation as well as our very own Republic Act No. 10066 or the National Cultural Heritage Act which both provides for the proper protection of Cultural properties on local or international basis. Methods used for this research started with the Significance Assessment Survey and Interview with key informants from various Cultural groups and personalities in the city. Next phase was the Physical documentation and assessment of selected cultural properties which includes actual site visits, on site sketches, photo documentation and ocular inspection for each property. Also part of the research method was to interview the current owners or management of each property to which conservation approach they see fit. After which, the selected buildings were categorized into three main groups of conservation, Maintenance and Preservation, Restoration and Reconstruction and Adaption and Rehabilitation. The categorization led to the formulation of two final projects for this research which are the Sinugdan Cultural Center and Village and Sugilanon Cultural Library.